2015
DOI: 10.1016/j.canlet.2015.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Activation of mucosal mast cells promotes inflammation-related colon cancer development through recruiting and modulating inflammatory CD11b+Gr1+ cells

Abstract: Mast cells (MCs) have been reported to be one of the important immunoregulatory cells in promoting the development of colitis-related colon cancer (CRC). It is not clear which MC subtypes play critical roles in CRC progression from colitis to cancer because mucosal mast cells (MMCs) are distinct from connective tissue mast cells (CTMCs) in maintaining intestinal barrier function under homeostatic and inflammatory conditions. In the current study, we found that MMC numbers and the gene expressions of MMC-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…Our group (and others) have reported the important role of mast cells in polyposis [24,25,26,27]. We also showed that chronic alcohol consumption results in increased mast cell numbers at the polyp site [11].…”
Section: Resultsmentioning
confidence: 55%
“…Our group (and others) have reported the important role of mast cells in polyposis [24,25,26,27]. We also showed that chronic alcohol consumption results in increased mast cell numbers at the polyp site [11].…”
Section: Resultsmentioning
confidence: 55%
“…The chronic inflammation that precedes tumorigenesis exhibits many of the same features as the acute, physiological process. For example, animal models have shown that inflammation causes activation of mucosal mast cells, which recruit CD11b(+)Gr1(+) myeloid cells from the circulation that help promote colitis-related colon cancer (122). …”
Section: The Role Of Inflammation In Cancer Initiationmentioning
confidence: 99%
“…A number of studies have indicated that inflammatory cells attracted to the sites of tumor lesions promote rather than inhibit tumor growth 23 . Further analyses have found that a variety of inflammatory cells such as macrophages, neutrophils, eosinophils, dendritic cells, and lymphocytes, etc., were involved in the control of tumor development and progression 24 , 25 . Growing evidence indicates that tumor cells could regulate the infiltration and activation of the host cells to promote their own survival and progression, and the white blood cells presented in the tumor microenvironment could promote tumor growth, angiogenesis, and metastasis via producing a series of growth factors, proteases, and angiogenic mediators 24 .…”
Section: The Etiology and Pathogenesis Of Ibcmentioning
confidence: 99%
“…Since the inner mucosal mast cells (MMCs) and connective tissue mast cells (CTMCs) play different intestinal barrier functions in the case of stability of internal environment and inflammation, it is difficult to determine which type of mast cells plays the key role in the development of CRC from colitis to colon cancer. Xu et al, 25 found that both numbers and gene expression levels of MMCs were increased in the mouse model of experimental induced CRC. After MMC activation, the production of mast cell protease 1 not only caused the accumulation of CD11b + Gr1 + inflammatory cells in the colon tissues but also regulated the activity of CD11b + Gr1 + cells to support the growth of tumor cells and to inhibit the activation of T cells.…”
Section: The Etiology and Pathogenesis Of Ibcmentioning
confidence: 99%